The Role of General Joint Courses in Promoting Citizenship Values among University Students from the Perspectives of Students at King Khalid University - Alhaj, Ali Albashir Mohammed; Alwadai, Mesfer Ahmed Mesfer (Technium Social Sciences Journal, 2023)
The present research paper intended to study the role of general joint courses in promoting citizenship values among university students from the perspectives of students at King Khalid University. Also, the study targeted to scrutinize the degree to which general joint courses curricula promote citizenship values among university students. The descriptive-analytical approach was adopted by the two researchers Moreover, the two researchers developed a questionnaire of thirteen items based on a five-point Likert Scale that was analyzed quantitatively by applying descriptive data. The two researchers chose a random stratified sample from different campuses and Colleges of King Khalid University in Abha,Algraa, Alomhalah, female students campus in Dhahran Aljanoub, and to mention a few). The purposive sample of the study consists of 1000 female and male undergraduates .The findings showed that the general average of the role played by general joint courses in promoting citizenship values among male and female students at King Khalid university came to a high degree with an arithmetic average of (4.48 and3.89 receptively in favor of male undergraduates. Also, the results have revealed that there are statistically significant differences between the mean responses of male and female university students regarding the role played by general joint courses in promoting citizenship values among King Khalid university students in favor of the sample of male students. The study recommends the necessary to carry out further exploration and closer examination of citizenship values among students and their effect on other variables such as the promotion of national values, and patriotism among students.